Calcium spirulan derived from Spirulina platensis inhibits herpes simplex virus 1 attachment to human keratinocytes and protects against herpes labialis - Mader, Julia; Gallo, Antonio; Schommartz, Tim; Handke, Wiebke; Nagel, Claus-Henning; Günther, Patrick; Brune, Wolfram; Reich, Kristian (Journal of allergy and clinical immunology, 2016)
Chronic infections with herpes simplex virus (HSV) type 1 are highly prevalent in populations worldwide and cause recurrent oral lesions in up to 40% of infected subjects. We investigated the antiviral activity of a defined Spirulina platensis microalga extract and of purified calcium spirulan (Ca-SP), a sulfated polysaccharide contained therein. The inhibitory effects of HSV-1 were assessed by using a plaque reduction assay and quantitative PCR in a susceptible mammalian epithelial cell line and confirmed in human keratinocytes. Time-of-addition and attachment experiments and fluorescence detection of the HSV-1 tegument protein VP16 were used to analyze the mechanism of HSV-1 inhibition. Effects of Ca-SP on Kaposi sarcoma–associated herpesvirus/human herpes virus 8 replication and uptake of the ORF45 tegument protein were tested in human retinal pigment epithelial cells. In an observational trial the prophylactic effects of topically applied Ca-SP were compared with those of systemic and topical nucleoside analogues in 198 volunteers with recurrent herpes labialis receiving permanent lip makeup. Ca-SP inhibited HSV-1 infection in vitro with a potency at least comparable to that of acyclovir by blocking viral attachment and penetration into host cells. Ca-SP also inhibited entry of Kaposi sarcoma–associated herpesvirus/human herpes virus 8. In the clinical model of herpes exacerbation, the prophylactic effect of a Ca-SP and microalgae extract containing cream was superior to that of acyclovir cream. These data indicate a potential clinical use of Ca-SP containing Spirulina species extract for the prophylactic treatment of herpes labialis and suggest possible activity of Ca-SP against infections caused by other herpesviruses.